Lack of Health Services Results in the Death of A Newborn Child in Senawang Village, Sumbawa (International Forum of Researchers and Lecturers, 2025)
The right to health services for residents of Senawang Village and evaluating the legal protection mechanisms that can be taken by residents of Senawang Village due to the lack of health services, the type of research used is empirical legal research. The approach method used is a sociological approach and a legislative approach, the type of data is primary data, secondary data and tertiary data. While the data collection techniques are in the form of interviews, literature, and documentation. Finally, with the analysis of the data obtained from this study, it can be concluded that the fulfillment of the right to a healthy life is a basic right that must be guaranteed, because health is part of the primary needs of every human being, which is clearly regulated in Article 28 H paragraph (1) of the 1945 Constitution and Law of the Republic of Indonesia Number 17 of 2023. However, the reality in the field shows that the implementation and implementation of these various policies is still far from expectations. This shows a gap between the ideal regulations on paper and their implementation in real life. Therefore, synergy between infrastructure policies and health services is crucial because without concrete improvements in the infrastructure sector, the goal of realizing equitable, fair, and high-quality access to health services for all Indonesians will be difficult to achieve.